Successful penile reimplantation and systematic review of world literature - Mensah, J.E.; Bray, L.D.; Akpakli, E.; Kyei, M.Y.; Oyortey, M. (African Journal of Urology, 2017)
Introduction There is paucity of case reports that describe successful non-microscopic penile reimplantation. We report a case of a self-inflicted penile amputation in an apparently normal patient with first psychotic break. Observation To report on a case of successful macrosurgical penile reimplantation, discuss the etiologies, surgical techniques and outcomes of world literature on penile reimplantation and an update of current trends in penile surgery. A 40 year-old male, father of 3 children and a proprietor of a nursery school with no prior pschiatric disorder was rushed to our trauma centre following a self-inflicted total penile amputation at its base with incomplete laceration of the scrotum due to command hallucination. He was immediately resuscitated and underwent a non-microscopic penile reimplantation and scrotal closure by an experienced urologist (JEM) by reattaching the dorsal vein, urethra, corporal, fascial and skin layers. A functional outcome with respect to voiding, penile erection and cosmesis was excellent. Conclusion Self-inflicted penile amputation may manifest as first psychotic break in apparently normal subjects. Though microscopic neurovascular reconstruction is the gold standard, macrosurgical reimplantation of penis by an experienced surgeon in the absence of a microscope yields satisfactory results. © 2017
Keywords: Penile amputation; Penile transplantation; Psychiatric illness; Reimplantation; Traumatic